Comparative Evaluation of the Ileum Microbiota Composition in Piglets at Different Growth Stages - Lu, Chang; Liu, Yadan; Ma, Yijia; Wang, Shu; Cai, Chunbo; Yang, Yang; Zhao, Yan; Liang, Guoming; Cao, Guoqing; Li, Bugao; Kim, Sung Woo; Guo, Xiaohong; et al. (Frontiers in Microbiology, 2021)
Intestinal microbiota can affect the intake, storage, and absorption of nutrients in the body, thereby greatly impacting the growth and development of animals. In addition to diet, the breed and growth stages of pigs could also affect changes in the intestinal microbiota. However, research on the developmental changes in the ileum microbiota of piglets remains unclear. In this study, the ileum microbiota of Jinfen White and Mashen piglets at different developmental stages were investigated using 16S rRNA sequencing. Physiologically, the villus height of the ileum decreased, and the crypt depth increased during the development of the two pig breeds. Additionally, the serum antioxidant factors in the Jinfen White piglets were significantly higher than in the Mashen piglets at the end of the nursing stage. A total of 690 OTUs belonging to 21 phyla and 286 genera were identified, of which Firmicutes and Proteobacteria were the dominant phyla during the development of both the Jinfen White and Mashen piglets, accounting for 90% of all OTUs. Further research revealed differences in dominant bacteria between the two breeds. With increasing age, the ileum microbial diversity increased, and in both the pig breeds, the proportion of Firmicutes increased, whereas the proportion of Proteobacteria decreased. Additionally, different samples were characterized by specific genera, and different KEGG pathways were predicted at certain developmental stages. Finally, the correlation between the ileum microbiota and physiological features was analyzed, and it was suggested that the host and environmental factors play important roles in the formation of the microbial community structure in piglets. In summary, we delineated the structure, function, and differences in ileum microbiota between Jinfen White and Mashen piglets during different growth stages. This study helps to understand the development of the intestinal microbiota in local and hybrid pig breeds.